Dobra starość zamożnej kobiety w okresie republiki (A good old age of a wealthy woman in the Roman Republic) - Dziuba, Agnieszka (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2014)
The authors of antique literary texts referring to the Roman Republic gave their attention to women inconsiderably. They were convinced, that woman’ space , according to the ancestors’rules, was a house (domus Romana). Despite of this opinion there are some references to old women in antique testimonia, both Greek and Latin. We can find there few mentions about Veturia, mother of Coriolanus, Cornelia, mother of Cracchi, Terentia, the wife of Marcus Tullius Cicero and Caerellia, the friend of orator. These information allow us to draw an optimistic conclusion regarding to the old woman’ status in Republican Rome. Indeed, we should declare that all of them were born in the upper class (nobilitas) and their familie were wealthy. These four women live during their old age independently, without the care of their male relatives. Probably all of them were widows. Veturia and Cornelia lost sons involved in politics of Rome. Terentia supplied her son Marcus in money. Although their Male relatives were in serious troubles, women did not bear any consequences because of it. They still were living in their splendid house, run rich estate and spent leisure hours Reading books from private libraries and meeting friends.They were persons of good reputation. Most important of all, Veturia’s behaviour and Cornelia’s way of life led to build a parenetic legend about these antique heroins.